Odpowiedzi

2009-10-11T10:17:13+02:00
Rozwiąż taki układ równań:
(x-3)^2+(y-1)^2=9
2y-x+1=0

Znajdziesz z ten sposób punkty A=(x_1,y_1) , \ B=(x_2,y_2) i podstaw pod wzór

2009-10-11T10:22:55+02:00
2y - x + 1 = 0
S = (2,-1)
r = 3

równanie okręgu:
(x - 2)² + (y + 1)² = 3²

2y - x + 1 = 0
x = 2y + 1

(x - 2)² + (y + 1)² = 9
(2y + 1 - 2)² + (y + 1)² = 9
(2y - 1)² + (y + 1)² = 9
4y² - 4y + 1 + y² + 2y + 1 = 9
5y² - 2y + 2 = 9
5y² - 2y - 7 = 0

Δ = 4 + 20*7 = 144
√Δ = 12

y₁ = (2 + 12)/10 = 1,4 x = 2y + 1 = 3,8
y₂ = (2 - 12)/10 = -1 x = 2y + 1 = -1

A = (1,4; 3,8)
B = (-1; -1)

|AB| = √[(1,4 + 1)² + (3,8 + 1)²] = √[(2,4)² + (4,8)²] = √[5,76 + 23,04] = √28,8 = 12√0,2